The effect of design on Removable Partial Dentures (Mustansiria Dental Journal, 2018)
The importance of properly designed removable partial denture cannot beoveremphasized, the execution of removable partial denture design may determine thesuccess or failure of the appliance inadequate design assures its facility.This study was done to confirm the effect of Kennedy classification and clinicalexamination on the removable partial design of group (A) dental technician and group(B) the dentists, and to be solved in future.The result show 36% of the cases were modified and changed according to thecases related variables this high and significant number of munificent reinforces theposition that RPD design should be decided and guided by the dentists.The study conducted the effects of Kennedy classification and clinicalexamination on the RPD design marked by the dentists after providing the clinicalexamination played a very important role in changing the RPD designs.